Oncogenic Viruses and Breast Cancer: Mouse Mammary Tumor Virus (MMTV), Bovine Leukemia Virus (BLV), Human Papilloma Virus (HPV), and Epstein–Barr Virus (EBV) - Lawson, James S.; Salmons, Brian; Glenn, Wendy K. (Frontiers in Oncology, 2018)
Background While the risk factors for breast cancer are well established, namely female gender, early menarche and late menopause plus the protective influence of early pregnancy, the underlying causes of breast cancer remain unknown. The development of substantial recent evidence indicates that a handful of viruses may have a role in breast cancer. These viruses are mouse mammary tumour virus (MMTV), bovine leukaemia virus (BLV), human papilloma viruses (HPVs) and Epstein Barr virus (EBV – also known as herpes virus type 4). Each of these viruses has documented oncogenic potential. The aim of this review is to inform the scientific and general community about this recent evidence. The evidence MMTV and human breast cancer -the evidence is detailed and comprehensive but cannot be regarded as conclusive. BLV and human breast cancer- the evidence is limited. However in view of the emerging information about BLV in human breast cancer, it is prudent to encourage the elimination of BLV in cattle, particularly in the dairy industry. HPVs and breast cancer -the evidence is substantial but not conclusive. The availability of effective preventive vaccines is a major advantage and their use should be encouraged. EBV and breast cancer -the evidence is also substantial but not conclusive. Currently, there are no practical means of either prevention or treatment. Although there is evidence of genetic predisposition, and cancer in general is a culmination of events, there is no evidence that inherited genetic traits are causal. Conclusion The influence of oncogenic viruses is currently the major plausible hypothesis for a direct cause of human breast cancer.